Effects of the medicinal plants Curcuma zedoaria and Camellia sinensis on halitosis control - Farina, Vitor Hugo [UNESP]; Lima, Ana Paula De [UNESP]; Balducci, Ivan [UNESP]; Brandão, Adriana Aigotti Haberbeck [UNESP] (Sociedade Brasileira de Pesquisa Odontológica - SBPqO, 2012)
Volatile sulphur compounds (VSC) are the gases mainly responsible for halitosis (bad breath). The aim of this research was to evaluate the effects of medicinal plants on halitosis control. Two commonly used plants were tested: Curcuma zedoaria and Camellia sinensis (green tea). These plants were prepared as an aqueous solution and used as mouthwashes, compared with a standard mouthwash of 0.12% chlorhexidine gluconate and a placebo (water). The experiment was conducted with 30 volunteers from the School of Dentistry of São Jose dos Campos, Univ. Estadual Paulista - UNESP, SP, Brazil. Each volunteer tested the four mouthwashes. The Cysteine Challenge Method, modified for this study, was used for initial breath standardization. Four breath assessments were conducted after volunteers rinsed orally with acetylcysteine: one before the test mouthwash was used; the second, one minute after its use; a third 90 minutes later; and the last 180 minutes later. The results showed that chlorhexidine gluconate lowered VSC production immediately, and that this effect lasted up to 3 hours, while the tested plants had immediate inhibitory effects but no residual inhibitory effects on VSC. We concluded that Curcuma zedoaria and Camellia sinensis, prepared as infusions and used as mouthwashes, did not have a residual neutralizing effect on VSC.
Keywords: Halitosis; Mouthwashes; Curcuma; Camellia sinensis